2012
DOI: 10.1017/s1041610212000890
|View full text |Cite
|
Sign up to set email alerts
|

Changes in depressive symptoms and functional disability among community-dwelling depressive older adults

Abstract: In depressed older persons, an improvement in depressive symptoms was associated with improved functional ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 36 publications
2
32
0
Order By: Relevance
“…The maximum score of the MMSE-KC is 30. In older adults, the association between depression and functional disability was identified in previous studies 23,24) . The Center for Epidemiological Studies-Depression Scale was used to evaluate depressive mood among participants in the present study 25) .…”
Section: Study Design and Participantsmentioning
confidence: 66%
“…The maximum score of the MMSE-KC is 30. In older adults, the association between depression and functional disability was identified in previous studies 23,24) . The Center for Epidemiological Studies-Depression Scale was used to evaluate depressive mood among participants in the present study 25) .…”
Section: Study Design and Participantsmentioning
confidence: 66%
“…In addition, adequate educational activities according to the individuals' educational level 11 are able to reduce the risk for dependence 27 . Concerning symptoms of depression and functional disability, national studies found an association with BADL and IADL 11,15 , whereas international studies found this association only with IADL 13 . This relationship may be due to the heterogeneity of the development of depression that results in the association between cognitive impairment and decline in the physical function.…”
Section: Discussionmentioning
confidence: 92%
“…This relationship may be due to the heterogeneity of the development of depression that results in the association between cognitive impairment and decline in the physical function. The mechanism for this cycle remains unknown; however, some behavioral and biological conditions are able to negatively influence functional ability 13 . In addition, depressive symptoms may have a negative impact on the quality of life and social relations of the elderly 11 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations